Legitimacy of Determination of Indigenous Papuan People Between The Papuan People's Assembly and The Papua Customary Council - Howay, Rein Ario (Journal of Law, Politic and Humanities, 2025)
The determination of Indigenous Papuans (Orang Asli Papua/OAP) within the Special Autonomy regime raises issues of institutional legitimacy between the Papuan People’s Assembly (MRP) and the Papuan Customary Council (DAP). Law Number 2 of 2021 defines OAP as individuals of Melanesian descent and/or those recognized by Papuan customary communities. This formulation creates a dual legitimacy framework, consisting of normative-legal legitimacy and customary legitimacy. This study aims to analyze the legal basis of authority in determining OAP status and the institutional relationship between MRP and DAP from a constitutional law perspective.This research employs normative legal research using statutory and conceptual approaches. Primary legal materials include Law Number 2 of 2021 and Government Regulation Number 106 of 2021, supported by doctrinal theories on legitimacy and authority. The analysis is conducted qualitatively through systematic and teleological interpretation.The findings indicate that MRP possesses legal-rational legitimacy derived from statutory attribution, while DAP holds traditional legitimacy rooted in constitutional recognition of customary law communities. This dual legitimacy may generate legal uncertainty if not clearly regulated. Therefore, an integrative regulatory model through a Special Regional Regulation is necessary, positioning DAP as a cultural verifier and MRP as the formal administrative authority in determining OAP status.